Utilização de metaheurísticas para balanceamento de carga em ambientes MapReduce - Pericini, Matheus Henrique Machado (2017)
With the increase in the number of data obtained by large companies, it was necessary to elaborate new strategies for the processing of this data in order to maintain the relevance of the information that they contain. One of the strategies that has been widely used is based on a programming model, called MapReduce, which uses division and conquest to process the data in a cluster of machines. Hadoop is one of the most consolidated implementations of the MapReduce model. But even such a strategy is subject to improvement. In it, the runtime depends on all the machines causing any overloaded machine to generate a delay in the delivery of the result. This overhead is caused by a problem commonly called Data Skew which consists of an unequal division of data, either by the size of the data or by the way it is divided. In order to solve this problem, we have proposed the MALiBU, an improvement of the execution strategy of Hadoop, which partitions the data between the machines using a meta-heuristic among them Simulated Annealing, Local Beam Search or Stochastic Beam Search. Experimental results showed improvements in the performance of Hadoop when using metaheuristics to distribute the data among the processing elements of the model, as well as among the three meta-heuristics evaluated, which has the best results.